Building Resilience Through Contemplative Practice : A Field Manual for Helping Professionals and Volunteers. - Patterson, Bobbi ([Place of publication not identified] : Routledge, 2019)
Recasting burnout as a crucial phase of service, Building Resilience Through Contemplative Practice uses real-world case studies to teach professionals and volunteers unique skills for cultivating resilience. Viewing service and burnout as interdependent throughout phases of stability, collapse, reorganization, and exploitation, the book uniquely combines elements of adaptive resilience theory with contemplative practices and pedagogies. Drawing on the author's extensive experience working at the intersection of service and contemplative practices, this is the first book to demonstrate how and why professionals and volunteers can reframe burnout as an opportunity for resilience-building service. User-friendly case studies provide tools, skills, and exercises for reconstructive next steps. Chapters address personal, group, and structural levels of service and burnout. Illuminating the link between adaptive resilience and burnout as a normal and useful phase of service, Building Resilience Through Contemplative Practice is a necessary resource for professionals and volunteers across a wide range of service settings.
List of Figures Acknowledgements Preface: Facing Burnout 1. Rewriting the Story of Service and Burnout 2. Contemplative Principles and Practices: Putting Adaptive Resilience to Work 3. Willingness/Not Willfulness 4. Not Taking In/Taking In 5. Moving Stability 6. Not All Up to Me/All Up to Me 7. The Edge of Earshot 8. Naming the Unnamed Index
OCLC-licensed vendor bibliographic record.
Keywords: Resilience (Personality trait); PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health